A Restoration Method for Distribution System Based on Projection of Multiple Microgrids - Shiyan ZHU; Yin XU; Jinghan HE; Ying WANG (Zhongguo dianli, 2024)
The participation of microgrids in distribution system restoration can improve the restoration effects and thereby enhance the system resilience. A restoration method for distribution system with multiple microgrids is proposed, which considers the microgrids' privacy and restoration preferences, and can coordinate the power generation resources of the distribution network and microgrids. Firstly, a coordination mechanism for multiple microgrids to participate in distribution network restoration based on virtual nodes and virtual flow decomposition is established to effectively protect the privacy of microgrids. Subsequently, a projection-based critical restoration information-sharing method is proposed to solve the restoration problem, and the vertex search is used to quickly obtain the projection domain and realize critical information interaction. And then, a two-layer coordinated restoration framework for the distribution network and microgrid is proposed, in which the lower microgrid provides limited information including restoration preferences and feasible domain to the distribution network; the upper distribution network makes overall decisions and sends the tie-line power obtained by the decision to the microgrid, and the lower microgrid uses the tie-line power as the constraints to determine the internal load restoration. Finally, based on the constructed power distribution system with multiple microgrids, the effectiveness and advantages of the proposed method is verified.